Static and dynamic impact of unified power flow controller (UPFC) in electric transmission system - Zulkifli, Dollah (2008)
Unified Power Flow Controller (UPFC) is a part of the Flexible AC Transmission System (FACTS). The main function of UPFC is to control the real and reactive power flow in transmission system, at the same time UPFC will control the voltage at the bus where it’s placed. The main purpose of this project is to analyses the static and dynamic impact of UPFC in transmission line. There have two software that used in this project which are MATLAB and PSCAD/EMTDC software. The MATLAB software used to get the data that can be used to model load flow by using PSCAD/EMTDC software. This modeling is called the steady state model (static). The model in PSCAD used to analyses the impact of UPFC in electric transmission line. For dynamic analyses, the model in steady state condition will apply fault. The analysis for the system is made and then the UPFC is applying to the system and the result will be analyzed. In this project the optimum location for placement of UPFC also has been discuss details. The simulation results show that the UPFC can control the active power, reactive power and the bus voltage which connected to UPFC.